Three-dimensional/four-dimensional transperineal ultrasound: clinical utility and future prospects - Salsi G; Cataneo I; Dodaro G; Rizzo N; Pilu G; Sanz Gascòn M; Youssef A (Dove Medical Press, 2017)
Ginevra Salsi,1 Ilaria Cataneo,1 Gaia Dodaro,1 Nicola Rizzo,1 Gianluigi Pilu,1 Mar Sanz Gascón,2,3 Aly Youssef1 1Department of Obstetrics and Gynecology, Sant’Orsola-Malpighi University Hospital, University of Bologna, Bologna, Italy; 2Department of Obstetrics and Gynecology, La Fé University Hospital, University of Valencia, 3Prenatal Diagnosis Unit, Casa del Salud University Hospital, Valencia, Spain Abstract: During the last decade, there has been a huge advancement in the use of transperineal ultrasound (TPU) in the field of obstetrics and gynecology. Its main applications in obstetrics include the monitoring of fetal progression in labor and recently the assessment of maternal pelvic dimensions, whereas in gynecology, TPU is at present widely used for the evaluation of the female pelvic floor, opening new boundaries for the assessment of pelvic floor disorders. The association of volumetric three-dimensional techniques has largely contributed to the remarkable progress that has occurred in the use of TPU. The aim of this paper is to offer an overview of the advantages, challenges and future perspectives of the use of TPU for women’s imaging. Keywords: transperineal ultrasound, 3D ultrasound, 4D ultrasound, TPU